2021
DOI: 10.1007/s00737-021-01153-0
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure of the Edinburgh Postnatal Depression Scale among perinatal high-risk and community samples in London

Abstract: Timely and accurate detection of perinatal mental health problems is essential for the wellbeing of both mother and child. Growing evidence has suggested that the Edinburgh Postnatal Depression Scale (EPDS) is not a unidimensional measure of perinatal depression, but can be used to screen for anxiety disorders. We aimed to assess the factor structure of the EPDS in 3 different groups of women: n = 266 pregnant women at high-risk of depression (“Perinatal Stress Study”), n = 471 pregnant women from a community … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…A lack of good or effective communication can easily lead to depression when pregnant women are experiencing considerable psychological fluctuations and pressure. [17,18] For primiparas with hypothyroidism and depression, appropriate psychological care can be given in clinical practice. Specific ways of providing this care include the following.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of good or effective communication can easily lead to depression when pregnant women are experiencing considerable psychological fluctuations and pressure. [17,18] For primiparas with hypothyroidism and depression, appropriate psychological care can be given in clinical practice. Specific ways of providing this care include the following.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the GAD-2 might not be appropriate to use at antenatal appointments, as it is not specific enough to the experience of pregnant women ( 37 ). In some instances HCPs might try to use aspects of EPDS to assess PNA as it has been suggested that the EPDS is sufficiently ‘bi-dimensional' in order to be able to accurately screen for PNA by several studies ( 38 , 39 ). However, there is some disagreement within the literature around this with critics of the EPDS suggesting that as it was originally designed to case find for PND it misses some of the nuances of PNA diagnosis, and is not able to adequately differentiate between symptoms of PND and PNA ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria for the DHCP included: contraindications to MRI, babies being too unwell to tolerate a scan and language difficulties preventing informed consent. 34 Toddlers were invited to the Centre for the Developing Brain, St Thomas’ Hospital, London, for neurodevelopmental assessment at 18 months post expected delivery date; appointments were made according to family availability as close as possible to this time point. Inclusion criteria for our follow-up study were: mother and baby attendance for MRI at term-equivalent age; completed toddler neurodevelopmental assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were enrolled in the Developing Human Connectome Project (DHCP, http://www.developingconnectome.org/), a neuroimaging-focused project, with eligibility criteria including pregnant women (aged ≥16 years) with a gestational age of 20–42 weeks, and newborn infants aged 24–44 weeks; infants enrolled in the DHCP had MRI at term-equivalent age. Exclusion criteria for the DHCP included: contraindications to MRI, babies being too unwell to tolerate a scan and language difficulties preventing informed consent 34. Toddlers were invited to the Centre for the Developing Brain, St Thomas’ Hospital, London, for neurodevelopmental assessment at 18 months post expected delivery date; appointments were made according to family availability as close as possible to this time point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation